Membranes for helium recovery: An overview on the context, materials and future directions - Sunarso, J.; Hashim, S.; Lin, Y.; Liu, Shaomin (Pergamon Press, 2017)
Helium demand is expected to double within the next two decades given its essential role as a cryogenic fluid and an inert gas in various technological applications whereas its production capacity only increases by 3% per year, leading to an inevitable rising price of helium in the near future. Despite its status as the second most abundant element in the universe, natural gas is currently the only most commercially viable source for helium extraction. However, the common practice of most natural gas industries, at the present, is to let its helium component remains mixed with other gases throughout the gas supply chain processes until the final venting step. Helium recovery unit should instead be integrated as the last unit operations component of the liquefied natural gas plant to exploit the extra revenue from helium recovery. This review aims to validate the potential of membrane technology to be utilized in such separation unit since membrane may provide significant economic incentive over the cryogenic distillation or pressure swing adsorption processes. Five different membranes, i.e., polymer, silica, zeolite, metal-organic framework, and mixed matrix metal-organic framework membranes are surveyed in terms of their helium or hydrogen separation permeation performance and the related stabilities during permeation processes. In the absence of helium permeation data, hydrogen permeation data is considered as the closest representative data for helium permeation due to their kinetic diameter proximity. Literature shows that silica membrane provides the best prospect in terms of helium permeability and selectivity to other large molecular gases due to its molecular sieving mechanism. Silica membrane also enables thermal activated diffusion and operation at high temperature, i.e., below 600–800 °C, over which silica matrix starts to densify. These advantages however are offset by the relatively complicated and time consuming synthesis and low reproducibility. Polymer membrane, although offering the most practical production process and scalability, exhibits relatively low helium permeability and selectivity. Zeolite membrane, albeit its high thermal and chemical stability, rarely possesses effective pore size smaller than the kinetic diameter of helium; thus making it more applicable as a substrate for another less stable but more selective membrane layer. Metal-organic framework membrane presents higher possibility to tailor its pore size than zeolite membrane due to the various possible combinations of inorganic clusters and organic linkers. Still, it shows relatively low helium to other large gases selectivity due to the flexibility imparted by the organic component. Mixed matrix membrane which incorporates metal-organic framework additive into predominantly polymer matrix, enhances helium to other large gases selectivity with respect to metal-organic framework membrane, though at the cost of reduced helium permeability. This review furthermore discusses all important issues related to the practical application of each type of membranes. It is hopeful that the insights provided by this review can promote more studies of membranes for helium separation.